2010
DOI: 10.1016/j.jfms.2009.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammatory and non-inflammatory diseases of the gastrointestinal tract in cats: Diagnostic advantages of full-thickness intestinal and extraintestinal biopsies

Abstract: An evaluation of histological findings in full-thickness biopsies from the gastrointestinal tract (GIT) and extraintestinal samples of 43 cats with chronic GIT disease signs was performed. In the majority of cases (46.5%) inflammatory bowel disease, ie, lymphocytic-plasmacytic enteritis/colitis (32.6%), eosinophilic gastroenterocolitis (11.6%) and mixed inflammatory infiltration (2.3%), was diagnosed. Furthermore, in four animals non-inflammatory mucosal band-shaped fibrosis (9.3%), and in 10 cats (23.3%) a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
11

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 21 publications
1
42
1
11
Order By: Relevance
“…Specifically, differentiating between inflammatory bowel disease (IBD) and small‐cell lymphosarcoma/alimentary lymphoma (SC‐LSA) can be difficult. These 2 SI diseases can be identical in history, presentation, physical examination findings, clinicopathologic changes, and ultrasonographic findings . Small intestinal histopathology is the gold standard for diagnosing and differentiating these 2 disease entities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, differentiating between inflammatory bowel disease (IBD) and small‐cell lymphosarcoma/alimentary lymphoma (SC‐LSA) can be difficult. These 2 SI diseases can be identical in history, presentation, physical examination findings, clinicopathologic changes, and ultrasonographic findings . Small intestinal histopathology is the gold standard for diagnosing and differentiating these 2 disease entities.…”
Section: Introductionmentioning
confidence: 99%
“…A debate has emerged within the field of veterinary gastroenterology in recent years over how to obtain diagnostic biopsy specimens from the feline SI, by endoscopy or full thickness surgical biopsy. Many recent studies have brought the diagnostic utility of endoscopic biopsy into question and shown high variation among histologic diagnoses in different segments of SI . The previous studies, however, have failed to consider the biopsy collection methodology used for each individual case.…”
Section: Introductionmentioning
confidence: 99%
“…57,97,125,135,252 In severely affected cats, this infiltrate may be accompanied by changes in the mucosal architecture, including villus atrophy and fusion, fibrosis, and lymphangiectasia. 57,97,125,135,252 In severely affected cats, this infiltrate may be accompanied by changes in the mucosal architecture, including villus atrophy and fusion, fibrosis, and lymphangiectasia.…”
Section: Correcting Anemiamentioning
confidence: 99%
“…A coloração bicolor foi a mais frequente (18%), seguida pela coloração característica (16,1%), típica de gatos siameses, e os da coloração preta (10,6%). Este dado seria importante no caso de mortes provocadas por ações maliciosas, que muitas vezes são motivadas por preconceitos ou crenças, como a relação do gato preto com o azar e a utilização deste em rituais de magia negra, embora no presente estudo não haja evidências da influência deste parâmetro na mortalidade (LOCKWOOD, 2005 agentes tóxicos e deletérios, como cumarínicos e pó de vidro (FRAZIER et al, 1999;MOTAS-GUZMÁN et al, 2003;FORRESTER;STANLEY, 2004;GWALTNEY-BRANT, 2007;XAVIER, 2008;MARLET;MAIORKA, 2010 (JERGENS, 2002;RECHE JUNIOR, 2003;GELBERG, 2007;KLEINSCHMIDT et al, 2010).…”
Section: Outros Processosunclassified
“…No presente estudo foram avaliados os casos de adenocarcinoma palpebral, glândula ceruminosa e nasal, sendo que o primeiro apresenta frequência baixa tanto na literatura quanto no presente estudo e os dois últimos apresentam maior frequência na literatura. No caso de adenocarcinomas pulmonares de origem bronquial, estas são as neoplasias pulmonares primárias mais frequentes do pulmão, contudo são raras, embora no presente estudo foi encontra a mesma frequência de adenocarcinomas e carcinomas pulmonares (broncogênico) (HAYES; MILNE; MANDELL, 1981, TOMLINSON et al, 1984CRIBB, 1988;LONDON et al, 1996;MOISAN;WATSON, 1996;MCENTEE, 1997;MUKARATIRWA;GRUYS, 2001;HOFFMAN et al, 2005;LANGLAIS et al, 2006).…”
Section: Outros Processosunclassified